Rekayasa Lalu Lintas Jalur Yos Sudarso dari Bank Papua Kota Timika Papua Tengah - Batto, Oktavianty (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
In Mimika Regency, the road network is categorized based on its function, namely arterial, collector, local, and neighborhood roads. One example of a very important arterial road in Mimika Regency is Jalan Yos Sudarso. This road has the status of a provincial road and functions as a primary artery. Connecting Bank Papua with the Education area, this road has characteristics in the form of an average traffic lane width of 6 meters with a four-lane divided configuration (4/2 D). In addition, this road is also equipped with sidewalks that provide additional facilities for pedestrians. The existence of Jalan Yos Sudarso as a main route demonstrates the importance of adequate road infrastructure management in Mimika Regency. Through proper maintenance and the application of appropriate traffic engineering, this road is expected to continue to optimally support economic activity and community mobility. Data processing and analysis using MKJI 1997. Based on MKJI 1997, the average degree of saturation is 0.1. So, Jl. Yos Sudarso direction Bank Papua - Education is ≥ 0.1 which is Forced / Bad.